Oxidação de substratos terpênicos catalisada por metais de transição(Co e Pd) suportados em sílica e porfirinas de manganês - Carla Nunes de Melo (2020)
In this work were developed catalytic systems aimed at obtaining high commercial value products from the transformation of compounds of natural origin. The developed processes present important advancements when obtaining compounds from the oxidation of poorly explored substrates such as valencene and isolongifolene. These substrates have low commercial value and are broadly found in its raw material. The proposed reactions were carried out as alternatives to the actual commonly used processes, following protocols aligned with the green chemistry’s principles, using mild reactions whenever possible, heterogeneous catalysts, green solvent, and molecular oxygen as the oxidizer. At the first moment, the oxidation of sesquiterpene valencene was appraised by using manganese porphyrins in homogeneous and heterogeneous systems. The use of traditional oxidizers such as PhIO, PhIO(OAc)2, and hydrogen peroxide in homogeneous catalysis was compared to the use of molecular oxygen as a green oxidizer alternative. The usage of molecular oxygen as an alternative oxidizer in those sorts of reactions leads to a cleaner process, complying with the green chemistry`s principles. Looking further ahead, it was possible to increase the yield of valencene-oxygenated products to 64% by adding minor quantities of imidazole additive to the reaction. The homogeneous catalysts were also used in the oxidation of isolongifolene, which allowed the obtaining of allylic oxidation products of its endocyclic double bond and epoxidation products with a yield of 70%. A heterogeneous catalyst was synthesized using a second-generation porphyrin on a functionalized SBA-15 silica. SBA-15-Im-MnP1 was also used in the oxidation reaction of valencene with molecular oxygen as the oxidizer. This arrangement proved to be efficient at obtaining nootkatone and valencene epoxidation, yielding 56% of those functionalized products. In order to expand current studies on the oxidation of the previously mentioned substrates, oxidation reactions of valencene and isologifolene were also carried out in systems using Pd/SiO2 as the Pd Solo-type heterogeneous catalyst. In this sort of system, only molecular oxygen is applied as the oxidizer, differing from actual systems found in the literature, in which co-oxidants addictives, nucleophiles, or cocatalysts are used. Regarding the isolongifolene, the usage of the green DEC solvent, combined with the use of a heterogeneous catalyst and molecular oxygen, represented a relevant route to obtain oxygenated products while also keeping in sight the principles of green chemistry. In this case, the maximum reaction yield was 94% to oxygenated products resulted from allylic oxidation and from the isolongifolene epoxidation. Besides, the system proved to be a potential route to 3-carene oxidation, monoterpene substrate used as a precursor in insecticides production. At last, valencene oxidation was performed using a cobalt-based catalyst also supported on silica (Co/SiO2). The proposed methodology is a simple and inexpensive alternative to obtain higher value-added products. The reactions were also performed in solvent-free systems, yielding around the same as those using solvents as to keep the pursuit of green processes in chemistry.